Value for money in transport infrastructure investment: An enhanced model for better procurement decisions. (March 2022) - Zhao, Jianfeng; Greenwood, David; Thurairajah, Niraj; Liu, Henry J.; Haigh, Richard
Abstract: This paper addresses the nebulous value for money (V f M) concept and its widely-criticised use in justifying the adoption of Public-Private Partnerships (PPPs) for transport infrastructure projects. It draws on the theories of value and identifies that value is generated in the interaction of the supply side (i.e., governments - as project sponsors and part of infrastructure delivery partnerships) and the demand side (i.e., end-users). In this sense, 'public' participation in transport is highlighted in the proposed framework to demonstrate that it is the combination of 'traditional' and 'public' V f M that together create a more meaningful V f M concept. To underpin the application of the framework, a dynamic V f M assessment process is developed that can facilitate the appropriate selection of a procurement method and assess its V f M throughout the project lifecycle. Unlike current examples, the framework is designed for both PPPs and their alternatives (e.g., conventional public sector procurement) and aligns ex-ante and ex-post V f M assessment. The enhanced model creates an opportunity for governments to recognise public V f M in transport interventions, shift their mindset from singular to multi-dimensional evaluation, and start to actually accumulate and exploit experience from past projects. As such, the contribution of this paper is twofold: (1) drawing upon theories of value, it depicts the ontology of V f M and addresses a missing ingredient in V f M assessment; and (2) it develops a holistic framework for the public sector to re-calibrate their V f M assessment policy when procuring transport projects. Highlights: Value for money (V f M) assessment that justifies the use of PPPs is controversial and have contributed to many failures. Theories of value reveal that value is generated in the interaction of the supply side (i.e., governments) and the demand side (i.e., end-users). The ontology of value for money proposed is a compound of traditional V f M and public V f M. In the context of transport, a pragmatic framework is proposed to shed light on V f M assessment. 'Public' participation in transport and the 'feeding' and 'retrospection' mechanisms are prioritised.